Analisis Pemilihan Region of Interest (RoI) pada Magnetic Resonance Spectroscopy (MRS) - Anita Nur Mayani; Gatot Murti Wibowo; Darmini Darmini (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: Magnetic Resonance Spectroscopy (MRS) is an advance examination of MRI which produces a spectra describes metabolic information of tissues. ROI setting was very important in producing the spectra with diagnostic value that called Full-Width at Half Maximum (FWHM). In clinical applications, Radiographers select several ROIs in obtaining FWHM values without any specific benchmark which in turn directly affects on the accuracy of staging brain tumor. This study aims to examine the FWHM profiles based on the ROI selections, and to determine the effect of selected ROIs to FWHM values.Methods: This research was a quantitative study with an experimental approach. Data were assessed by an expert Radiographer during a period of 30 days on June 2016 in Radiology Department of Siloam Kebon Jeruk Jakarta Hospital using a specific bottle phantom MRI 2000 ml. The phantom was scanned with 1.5 Tesla MRI scanner, wuth various selection of the ROIs sized 20 mm, 25 mm, 30 mm, 35 mm and 40 mm at the centre position, 12 o'clock position, 3 o'clock position, 6 o'clock position and 9 o'clock position. Data was analyzed using linier regression test of SPSS V.16 software. The confident interval of influence of the ROI size in producing FWHM values was 95%.Results: The results showed the optimum FWHM values, 12-20, produced from the ROI size of 20-30 mm at the centre position. Regression analysis showed significant result (p-value 0.05), which was null hypothesis was rejected. It can be concluded that the ROI size setting effected on the resulted  FWHM values. The smaller ROI size, FWHM value will decrease with higher homogeneity and vise versa.Conclusion: Optimum FWHM value was produced by ROI size of 20 – 30 mm at the centre position. There was influence of ROI size setting to FWHM value.